Example of Utilizing RobotStudio for Simulating a Solution in the Medical Sector - Natalia DANIEL (natalia.daniel@wat.edu.pl); Wojciech KACZMAREK (wojciech.kaczmarek@wat.edu.pl); Jarosław PANASIUK (jaroslaw.panasiuk@wat.edu.pl) (Problemy Mechatroniki)
In recent years, there has been a growing interest in the use of robots in medicine. The article discusses, in general terms, exemplary robot solutions in the medical sector. Specific applications of robots during the COVID-19 pandemic, such as swab collection robots and telemedicine robots, are also presented. The aim of the article is to present the possibilities of the RobotStudio environment as a tool for presenting ideas related to the use of collaborative robots (cobots) in medicine. A partial review of robotic arm solutions was conducted, and an sample computer simulation was performed using RobotStudio, in which a robot administers a vaccine to a patient. The findings suggest that RobotStudio can be an effective tool for presenting applications of collaborative robots in medicine, especially for repetitive tasks, such as administering vaccines. The presented simulation is an example of using a collaborative robot to present the authors’ own concept within the medical sector, where access to equipment is limited.